KIF18A induces the EMT process of hepatoma cells through the 5-LOX-dependent arachidonic acid pathway - Yibo Wang; Tao Cai; Yajie Chen; Wenpeng Liu; Baowang Liu; Xin Zhao; Yang Wang; Jinglin Cao; Qiang Zeng (PLoS ONE, 2025)
The high morbidity and mortality rates of liver cancer prompt us to constantly explore new therapeutic strategies. The arachidonic acid metabolism-related pathways play a crucial regulatory role in the growth, invasion and angiogenesis of liver cancer cells, thus becoming a key entry point in liver cancer research. This study aims to explore the role of KIF18A in the epithelial-mesenchymal transition (EMT) of liver cancer cells through the 5-LOX-dependent arachidonic acid pathway, and to construct a prognostic model to predict the prognostic risk of patients with hepatocellular carcinoma (HCC). Through bioinformatics techniques, we screened out prognosis genes related to arachidonic acid metabolism in HCC and constructed a prognostic model of HCC. We evaluated and verified the model, and analyzed the functional enrichment analysis and PPI network analysis of key arachidonic acid metabolism-related genes, and screened out the key prognostic gene KIF18A. Experimental results showed that the expression level of KIF18A in liver cancer cells was significantly higher than that in normal liver cells, and the high expression of KIF18A was associated with the poor prognosis of patients with liver cancer. The overexpression of KIF18A could significantly promote the proliferation, invasion and migration abilities of liver cancer cells, while the knockdown of KIF18A inhibited these cellular behaviors. In addition, KIF18A could promote EMT of liver cancer cells, downregulate E-cadherin and upregulate the expression of N-cadherin. We also found that KIF18A could induce the upregulation of 5-LOX expression and increase the levels of arachidonic acid metabolites, while the 5-LOX inhibitor U73122 could reverse this effect. Therefore, KIF18A may promote the proliferation, invasion, and EMT of liver cancer cells by activating the 5-LOX-dependent arachidonic acid pathway. This study provides a new strategy for the prognostic assessment and targeted therapy of HCC and reveals the important role of KIF18A in the development of liver cancer.